Effect of wind exposure on stem stand characteristics and anatomical features of fir trees - Topaçoğlu, Osman; Keleş, Seray Özden (BioResources, 2025)
Wind causes significant damage to trees in many parts of the world, affecting tree growth, morphology, and forest ecology. The risk of wind damage is believed to be increasing due to global climate change. In this study, effects of wind exposure on the anatomical traits and stem stand characteristics in stands of Trojan fir trees (Abies nordmanniana subsp. equi-trojani [Asch. and Sint. ex Boiss] Coode and Cullen) were investigated. The study was conducted on Ilgaz Mountain, northwest of Kastamonu City, Türkiye. The wind-damaged and undamaged Trojan fir trees were identified, and their wood anatomical and stand characteristics were compared. Tree-ring width and wood anatomical traits (tracheid length, tracheid lumen area, tracheid wall thickness, and ray width) were higher in undamaged fir trees than in wind-damaged fir trees. It has been suggested that prolonged exposure to wind in Trojan fir trees may result in the development of changes in wood anatomical traits and tree rings such that more wind-exposed trees could produce shorter and thinner tracheid traits, because tracheid cell development processes could be negatively affected by wind exposure. However, wind-damaged Trojan fir trees had greater stem height and diameter, slenderness ratio, and stand basal area than undamaged fir trees. In this study, tall trees tended to be the most vulnerable and least resistant to wind damage.
Keywords: tree stability; wood anatomy; tree selenderness; wind damage; morpho-anotomical response; TP248.13-248.65; Biotechnology